Learning from Returned Products in a Closed Loop Supply Chain: A Systematic Literature Review - Ilkka Ritola; Harold Krikke; Marjolein C.J. Caniëls (Logistics)
Product returns are a source of valuable information that can be used by firms and supply chains to improve products, services, and decision making. However, firms are struggling to maximize the value of this information, and the extant scholarly literature is scattered among various research streams. Using a systematic literature review, the state-of-the-art of product returns informational value research and limitations in the current body of work were examined and future directions for research suggested. Three types of informational value were identified, namely operational information, product related information, and customer-related information, along with four value-creating factors, namely strategic information system (IS) decisions, organizational learning, information sharing, and technological solutions. Implications for practitioners are discussed. Lastly, the limitations are discussed, along with recommendations and directions for future research work.